Rising China and world order - Zhang, Yunling, 1945- (World Scientific, 2010)
"This book consists of the author's writings on China's perspective and policy with regard to its foreign relations and engagement of regional and global affairs. It covers issues ranging from the post-Cold War world order, China-US relations, the significance of China's rise, the North Korean nuclear crisis and China's policy, and China's relations with its neighbors in a new context. Rising China and World Order provides insights into China's interests and policy from an eminent Chinese scholar."--Publisher's website, Nov. 8, 2010.